Effects of fluid inertia forces in ferrofluid lubricated circular stepped squeeze films – Shliomis model. Issue 6 (12th September 2016) - Lin, Jaw-Ren; Hung, Tzu-Chen; Hu, Shu-Ting
Abstract : Purpose: This paper aims to study the inertia squeeze film characteristics between ferrofluid-lubricated circular stepped disks. Owing to the development of modern machine systems, the application of ferrofluids has received great attention. Because the circular disks are a special situation of circular stepped squeeze films, a further study of fluid inertia force effects on the ferrofluid-lubricated circular stepped squeezing mechanism is motivated. Design/methodology/approach: On the basis of the ferrohydrodynamic flow model of Shliomis incorporating the momentum integral method, the effects of fluid inertia forces in ferrofluid-lubricated circular stepped squeeze films in the presence of external magnetic fields are investigated in this study. Analytical solutions of squeeze film performances are derived. Findings: The fluid inertia force effects provide an increased load capacity and a longer squeeze film time for the ferrofluid-lubricated circular stepped squeeze film, especially for a larger value of the inertia parameter, the Langevin parameter and the volume concentration and a smaller value of the radius ratio and the step height ratio. Originality/value: For engineering applications, numerical tables for squeeze film loads of circular stepped disks are also provided in this paper.